Risk factors for calcaneal fracture-related infection in open reduction and internal fixation: a retrospective cohort - Santos, Eduardo Cezar Silva dos; Ferreira, Renato de Oliveira Arnaud; Falcão, Sabra Mariela Fernandes; Araújo Pires, Eduardo Araújo Pires; Rosemberg, Dov Lagus; Araújo da Silva, Daniel; Katayama, Martha Lúcia Silva; Rosa, Felipe Daniel Plata; Freitas, Cláudia Diniz (Journal of the Foot & Ankle, 2025)
Objective: To identify independent risk factors for calcaneal fracture-related infection (FRI) in open reduction and internal fixation (ORIF). Methods: Retrospective and observational study using data extracted from the TriNetX international platform, including patients of both sexes with a confirmed diagnosis of calcaneal fracture submitted to surgical treatment with ORIF, with a 1-year follow up. An adjusted multiple logistic regression test was used to identify independent variables, and the Kaplan-Meier and Log-Rank tests were used to assess disease-free survival. Results: In total, 2,830 patients with a mean age of 50 years (SD ± 15) were evaluated, most of them men, 1,788 (63.8%). One hundred eighty-one patients had FRI within one year after surgical treatment. The following variables were independent risk factors for FRI: smoking [OR 1.8 (CI 0.02;0.06), p = 0.0001], alcohol abuse [OR 1.6 (CI 1.0;2.6), p = 0.045], chronic kidney disease [OR 2.23 (CI 1.13;4.39), p = 0.017], overweight [OR 2.8 (CI 1.34;5.89), p = 0.004], fall from height [OR 2.18 (CI 1.47;3.25), p = 0.0001] and open fracture [OR 2.13 (CI 1.07;4.23), p = 0.026]. Conclusion: Smoking, alcohol abuse, chronic kidney disease, overweight, fall from height, and open fracture were independent risk factors for infection. Level of evidence II, observational study